(untitled) (Biological Sciences - PJSIR, 2000)
N-(Substituted benzoyl) thiosernicarbazides lla-e were treated with sodium hydroxide solution to give 3-aryl-S- e mercapto-4H-i ,2,4-triazolc 111a-e which were subjected to Mannich Reaction in presence of2-0Cll;, 4-NOz and 2- OeH) substituted anilines to give 3-aryl 7H, 6-(aryl) SH-I,2,4-triazolo [3,4-b]-I,3,S-thiadiazines IVa-h. The com- pounds, IVa-h were compared with oxytetracycline and ampiclox (standard antibiotics) for their antibacterial activity.